2012
DOI: 10.1186/1550-2783-9-32
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrient intake on antioxidant capacity, muscle damage and white blood cell count in female soccer players

Abstract: BackgroundSoccer is a form of exercise that induces inflammatory response, as well as an increase in free radicals potentially leading to muscle injury. Balanced nutritional intake provides important antioxidant vitamins, including vitamins A, C and E, which may assist in preventing exercise-related muscle damage. The purpose of the present study was to determine the effect of macro/micronutrient intake on markers of oxidative stress, muscle damage, inflammatory and immune response in female soccer players.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 56 publications
3
69
1
3
Order By: Relevance
“…Considering this recommendation, the women's total carbohydrate intake was much lower than the recommended (54%±5.1 p<0.05). Other studies have also reported insufficient carbohydrate intake by female athletes, ranging from 48 to 55% of the total energy requirement 5,6,21 . The recommended carbohydrate intake for all athletes is 6 to 10 g/kg/d 7 to maintain glycogen synthesis and sufficient muscle and hepatic energy reserves.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this recommendation, the women's total carbohydrate intake was much lower than the recommended (54%±5.1 p<0.05). Other studies have also reported insufficient carbohydrate intake by female athletes, ranging from 48 to 55% of the total energy requirement 5,6,21 . The recommended carbohydrate intake for all athletes is 6 to 10 g/kg/d 7 to maintain glycogen synthesis and sufficient muscle and hepatic energy reserves.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the lipid hydroperoxides are unstable with the presence of metal ions and it is decomposed to a variety of reaction products, whereas conjugated dienes take up O 2 and form peroxyl radicals or lipid hydroperoxides (Jenkins, 2000). Nonetheless, one limitation of the present study could be related with content of antioxidant nutrition (Gravina et al, 2012), which could not be fully controlled. This may explain the significantly higher levels of thiobarbituric acid reactive species for SMW with respect to placebo at the basal period.…”
Section: Discussionmentioning
confidence: 84%
“…First, the basal plasma thiobarbituric acid reactive species levels were significant different between both groups, suggesting that some variables were not full controlled such as the antioxidant nutrition content (Gravina et al, 2012). Second, in spite of main antioxidant enzymes were measured at the present study, other antioxidant markers, such as total antioxidant capacity or plasma/erythrocyte glutathione levels, were not measured to have a whole understanding of SMW antioxidant effect.…”
Section: Discussionmentioning
confidence: 92%
“…Also, some earlier studies have reported the beneficial effects of n-3 and n-6 polyunsaturated fatty acids on oxidative stress and antioxidant capacity (20,21). However, some other researchers have revealed that n-3 FA available in fish oil not only could not significantly reduce antioxidant parameters in cardiomyocytes, but also enhanced MDA plasma concentrations in the athletes (22,23).…”
Section: Discussionmentioning
confidence: 99%